2023
DOI: 10.3390/pharmaceutics15020522
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles of Probiotics: Shedding Light on the Biological Activity and Future Applications

Abstract: For many decades, the proper functioning of the human body has become a leading scientific topic. In the course of numerous experiments, a striking impact of probiotics on the human body has been documented, including maintaining the physiological balance of endogenous microorganisms, regulating the functioning of the immune system, enhancing the digestive properties of the host, and preventing or alleviating the course of many diseases. Recent research, especially from the last decade, shows that this health-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 156 publications
0
13
0
Order By: Relevance
“…The researchers confirmed that extracellular vesicles (EVs) can be taken up by colon cancer cells and inhibit their growth by inducing apoptosis 69 . Extracellular vesicles produced by L. paracasei (LpEVs) have been demonstrated to reduce colorectal cancer cell proliferation and induce apoptosis through the PDK1/AKT/Bcl-2 pathway 70 .…”
Section: Discussionmentioning
confidence: 93%
“…The researchers confirmed that extracellular vesicles (EVs) can be taken up by colon cancer cells and inhibit their growth by inducing apoptosis 69 . Extracellular vesicles produced by L. paracasei (LpEVs) have been demonstrated to reduce colorectal cancer cell proliferation and induce apoptosis through the PDK1/AKT/Bcl-2 pathway 70 .…”
Section: Discussionmentioning
confidence: 93%
“…54 Although the EV yield of probiotics, especially Gram-positive bacteria, is lower, it can be further improved by modular production and normative modifications, which are applicable to probiotics in the food industry. 55,56 Our study investigated the effect of culture condition on LGG-EV and provided a theoretical basis for subsequent large-scale production of LGG-EV, which has potential as a nonproliferative biological agent in the health field.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vehicles (EVs) produced by probiotics have garnered significant attention due to their potential biological activity and future applications. These vesicles serve as a means of transporting various macromolecules, including lipids, polysaccharides, proteins, and nucleic acids, and have been associated with health-inducing properties [ 67 ]. Previous research has demonstrated that EVs play a role in modulating inflammatory responses and immune function.…”
Section: Mechanisms Of Action Of Ngpsmentioning
confidence: 99%